Profile of cleft lip and palate patients at Wits Oral Health Centre Cleft Clinic - Carrim, Fatima (My University, 2021)
Objectives: To determine the clinical profile of patients with orofacial clefts (OFC) who presented at the Wits Oral Health Centre (WOHC) Cleft Clinic from 1 January 2013 to 31 December 2019. Materials and Methods: A cross-sectional, retrospective record review of OFC data was conducted. Demographic and clinical information of patients with OFC was collected. STATA version 15 was used to analyse the data and statistical tests were conducted at 5% significance level. Results: 133 records were analysed. The median age at the first consultation was 6 years (IQR =3-11 years). The majority were males (n=68, 51.13%), whilst 48.87% (n=65) were females. Most patients were South Africans 91.73% (n=122,), and the majority were African blacks (67.67%). A statistically significant difference (p<0.05) was found in gender and racial distribution of OFC. Conclusions: WOHC Cleft Clinic is providing services to a growing number of patients with OFC. The study findings should assist in planning service for these patients.
A research report submitted to the Department of Orthodontics, School of Oral Health Sciences, Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Dentistry